Lichen Sclerosus and Sexual Dysfunction: A Systematic Review and Meta-Analysis. Issue 11 (15th September 2022) - Pope, Rachel; Lee, Min Ho; Myers, Anna; Song, Junmin; Abou Ghayda, Ramy; Kim, Jong Yeob; Hong, Sung Hwi; Lee, Se Bee; Koyanagi, Ai; Jacob, Louis; Smith, Lee; Shin, Jae Il
Abstract: Background: Lichen sclerosus (LS) is a common autoimmune dermatological condition that is often under-diagnosed in women and has been documented to affect quality of life and sexual function. Aim: To determine the prevalence of sexual dysfunction among women with vulvar lichen sclerosus. Methods: The authors conducted a systematic review and meta-analysis of the existing research on LS and sexual function in database including PubMed using search terms: lichen sclerosus OR vulvar lichen sclerosus OR vulvar lichen sclerosus et atrophicus OR kraurosis vulvae) AND (sexual function OR sexual functions OR sexual disorder OR sexual disorders OR sexual activity OR sexual activities OR sexual dysfunction OR sexual dysfunctions OR dyspareunia OR vaginismus). Outcomes: Nearly 60% of women with lichen sclerosus suffer from sexual dysfunction. Results: Two hundred and ten studies were initially identified. Twenty-six articles met inclusion criteria and 3 were excluded as they did not relate to sexual function, were regarding a surgical or medical intervention and sexual dysfunction and one was a review article. Therefore, 23 studies were included in the final analysis resulting in a cumulative 486 participants with LS with 208 patients experiencing any kind of sexual dysfunction. Meta-analysis presented prevalence of sexual dysfunction among LS patients as 59% (95% CI: 48 – 70%). Dyspareunia or generalized pain with intercourse was the most commonly reported type of dysfunction. Clinical Implications: Discussing sexual concerns with women with LS could empower them to seek treatment. Strengths and Limitations: Few articles met criteria for inclusion. Conclusion: A large proportion of women with LS experience sexual dysfunction. More research is needed, especially that which includes biopsy-proven LS and validated tools on sexual function.